2019
DOI: 10.1097/acm.0000000000002845
|View full text |Cite
|
Sign up to set email alerts
|

“Yes, I’m the Doctor”: One Department’s Approach to Assessing and Addressing Gender-Based Discrimination in the Modern Medical Training Era

Abstract: A cross-sectional study of gender-based discrimination and bias during residency training Many studies have shown that both residents and attending physicians are unhappy in their work. One possible explanation for resident physician unhappiness is a suboptimal learning and working environment. We are attempting to better understand the learning and working environment for resident physicians within the Partners system. As a resident physician, you are invited to complete the following survey on your workplace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 17 publications
0
28
1
1
Order By: Relevance
“…1 Studies from the 1990s reported that female medical students, 2 residents, 3 and practicing clinicians 4,5 experience sexual harassment by patients and more recent studies confirmed this as an ongoing problem. [6][7][8][9] Although all these studies describe the scope of the problem, clear guidance on how to address it is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies from the 1990s reported that female medical students, 2 residents, 3 and practicing clinicians 4,5 experience sexual harassment by patients and more recent studies confirmed this as an ongoing problem. [6][7][8][9] Although all these studies describe the scope of the problem, clear guidance on how to address it is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey of 371 surgery, anesthesia, and internal medicine residents at Massachusetts General Hospital, 61% of participants reported personal experience of gender-based discrimination during training, with women more likely than men to have such experiences (93% vs 24%). 15 While the most frequent sources of gender-based discrimination were patients and nursing staff, attendings and co-residents were also identified as sources, with women more likely than men to cite diminished responsibility, diminished patient and provider trust, inappropriate verbal exchange, being asked to perform nonmedical tasks, and sexual harassment as forms of gender-based discrimination (all P< 0.04). 15 While this data specifically relates to a training setting, it is undoubtedly not limited to this period of a woman's career and occurs in faculty years and beyond.…”
Section: Opportunitiesmentioning
confidence: 97%
“…14 Simply recognizing and tracking gender-based discrimination are important first steps to addressing this problem, with forming a task force, implicit bias training, and improving reporting mechanisms critical to making substantial change. 15 In terms of family planning, a recent perspective piece by Ortiz et al advocated for adopting a standard parental leave policy of 8 weeks paid without extending training or impacting board certification to promote gender equity in training and pave the way for greater retention, advancement, and leadership roles for women in medicine. 18 Now, through the continued work of these and other advocates, change is finally on the horizon.…”
Section: Opportunitiesmentioning
confidence: 99%
“…The italicized quotes that follow are reflections from this team.The article starts by describing the pervasiveness of gender discrimination and sexual harassment in medicine, citing studies that reveal most women clinician-researchers and almost all women residents have experienced gender discrimination during their careers, with one-third experiencing sexual harassment. 3,4 Discrimination must be ubiquitous to support such statistics, however the frequency uncovered by this work surprised even some members of Dr Russell's research team and department. This is understandable, as it is easiest to believe that "almost all" means everyone else, rather than the more logical truth that it includes us all.…”
mentioning
confidence: 88%